1983
DOI: 10.1079/bjn19830080
|View full text |Cite
|
Sign up to set email alerts
|

The effect of high-protein and high-carbohydrate diets on [125I]iodoinsulin binding in skeletal muscle plasma membranes and isolated hepatocytes of rainbow trout (Salmo gairdneri)

Abstract: 1.[12SI]iodoinsulin-binding studies in the presence of a concentration range of bovine insulin were conducted to establish specific insulin-binding levels in skeletal muscle plasma membranes and isolated hepatocytes of rainbow trout (Salmo guirdnert) reared on control, high-protein or high-carbohydrate diets.2. Negative co-operativity was observed and receptor concentrations and apparent dissociation constants established for each preparation.3. No differences of specific binding attributed to diet were detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

1989
1989
1998
1998

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…The number of binding sites on salmonid hepatocytes, and other binding indices are, however, similar to our previous observations on the salmons as well as to the data obtained on some other fish species (reviewed by Mommsen and Plisetskaya 1991) and on frog by Scapin and Incerpi (1992). In contrast, Ablett et al (1983) reported that parameters of insulin binding by trout hepatocytes are similar to that described in mammals.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The number of binding sites on salmonid hepatocytes, and other binding indices are, however, similar to our previous observations on the salmons as well as to the data obtained on some other fish species (reviewed by Mommsen and Plisetskaya 1991) and on frog by Scapin and Incerpi (1992). In contrast, Ablett et al (1983) reported that parameters of insulin binding by trout hepatocytes are similar to that described in mammals.…”
Section: Discussionsupporting
confidence: 86%
“…Binding of insulin to isolated fish liver cells has been reported only by Ablett et al (1983), and Segner et al (1993) but to our knowledge, this is the first study which has examined insulin processing by fish liver cells. Mammalian insulin retains its full biological potency toward fish liver (reviewed by Mommsen and Plisetskaya 1991) and has been reported to be preferable over piscine insulins in 125I insulin binding studies (reviewed by Guti6rrez and Plisetskaya 1991a,b).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Amino acids, rather than glucose, are the major stimuli for insulin release from the islet cells in teleosts (Ablett er ul. 1983) . Ablett et al (1983) suggested that high-protein diets chronically elevate insulin in salmon (Sulmo gairdneri) and reduce insulin binding by liver and muscle membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Muggeo et al (1979), when comparing insulin receptors from a variety of vertebrate species, described characteristics of insulin binding to erythrocytes of rainbow trout (Oncorhynchus mykiss). With respect to the liver of teleosts, Ablett et al (1983) were the first to study the specific interaction of insulin with hepatocytes. Kinetic data on insulin binding sites in teleostean liver including Scatchard plot analysis, saturation and displacement experiments, have been published to date only for the two closely related carnivorous species, coho salmon, (Oncorhynchus kisutch, and rainbow trout as well as for the scorpionfish (Scorpaena porcus, Leibush andBondareva 1991, cited by Gutierrez and.…”
Section: Introductionmentioning
confidence: 99%